x=y-8

-x-y=0

1. Look for a variable that is isolated. In this problem we see x=, so we will use that equation. Put a box around y-8, that is the expression we will be substituting in for x.

2. Substitute y8 in for x in the second equation. NOTE: There is a negative in front of x, so we need to put parenthesis: -(y-8)-y=0.

3. Solve for y. Make sure you use the distributive property! -y+8-y=0 -> -2y +8 = 0 -> -2y=-8 -> y=-4

4. Now that we know y=-4, plug your answer into x = y+8. x= -4 + 8, so x=4!

5. Final answer? (4, -4)!